Application of compression optical coherence elastography for characterization of human pericardium: A pilot study. Issue 3 (28th November 2022) - Zaitsev, Vladimir Y.; Sovetsky, Alexander A.; Matveyev, Alexander L.; Matveev, Lev A.; Shabanov, Dmitry; Salamatova, Victoria Y.; Karavaikin, Pavel A.; Vassilevski, Yuri V.
Abstract: The recent impressive progress in Compression Optical Coherence Elastography (C‐OCE) demonstrated diverse biomedical applications, comprising ophthalmology, oncology, etc. High resolution of C‐OCE enables spatially resolved characterization of elasticity of rather thin (thickness < 1 mm) samples, which previously was impossible. Besides Young's modulus, C‐OCE enables obtaining of nonlinear stress–strain dependences for various tissues. Here, we report the first application of C‐OCE to nondestructively characterize biomechanics of human pericardium, for which data of conventional tensile tests are very limited and controversial. C‐OCE revealed pronounced differences among differently prepared pericardium samples. Ample understanding of the influence of chemo‐mechanical treatment on pericardium biomechanics is very important because of rapidly growing usage of own patients' pericardium for replacement of aortic valve leaflets in cardio‐surgery. The figure demonstrates differences in the tangent Young's modulus after glutaraldehyde‐induced cross‐linking for two pericardium samples. One sample was over‐stretched during the preparation, which caused some damage to the tissue. Abstract : New application of Compression Optical Coherence Elastography (C‐OCE) is demonstrated: characterization of thin membrane‐like tissues, suggesting a nondestructive alternative to conventional tensile tests. Here, C‐OCE is applied to human pericardium, from which autologous aortic‐valve leaflets are prepared for surgical replacement. C‐OCE easily distinguishes correctly prepared pericardium (by Ozaki protocol) from incorrectly prepared samples. For this, C‐OCE ability to obtain nonlinear stress–strain curves is crucial. Thus, besides widely discussed oncologic and ophthalmic problems, thin‐sample characterization may be another important application of C‐OCE.